IMPLEMENTATION OF BIDIRECTIONAL VOICE COMMUNICATION BETWEEN NORMAL AND DEAF & DUMB PERSON - Saraswathi, V.; Sushmitha, S.; Saranya, C. (IJRDO -Journal of Computer Science Engineering, 2016)
In the existing system there is no hand recognition system to indicate the actions. In the proposed system, Android Application is employed to grab Images through Camera. The main idea of the paper is to understand the communication of the deaf and dumb people. Deaf and Dumb people will show their Hand Gesture in front of Camera and it sends to the Server. Server processes the Hand Gesture and corresponding Voice alert is played in the Normal Person side (Android). In the modification, Normal Person will speak through the Android Application, which recognizes the Voice input and it converts into Hand Gesture image to the Deaf & Dumb Person. We can also transfer the Hand Gesture input by deaf & dumb person to multiple Android normal People. We can Establish Two way Communication between Deaf & Dumb child with normal Child.